1999
DOI: 10.1023/a:1023092627223
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sleep disturbances are regarded as a common clinical feature in autistic children. This concept is based primarily on informal observations or studies conducted with questionnaires. In this study we compared data obtained by questionnaires to that obtained with actigraphy. Among 22 autistic children, 12 were reported as having sleep problems and 8 patients completed 72 hours actigraphy. While the employment of questionnaires disclosed that autistic children had an earlier morning awakening time and multiple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(20 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…A small to medium effect size (.36) for TST was observed at week 8. The disparate findings between parent-report questionnaires and actigraphy have been reported elsewhere [14,15,33,64]. Again there may be several explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A small to medium effect size (.36) for TST was observed at week 8. The disparate findings between parent-report questionnaires and actigraphy have been reported elsewhere [14,15,33,64]. Again there may be several explanations for these discrepancies.…”
Section: Discussionmentioning
confidence: 67%
“…Actigraphy is a reliable objective method for measuring sleep-wake patterns, including timing, continuity, and sleep duration, which can be used in the home. Although actigraphy data and parent-completed questionnaires have not always been consistent, actigraphy data have reflected sleep disturbances in children with ASD, particularly when compared to their typically developing counterparts [13-15]. …”
Section: Introductionmentioning
confidence: 99%
“…However, our study is not the first study to report relatively comparable sleep in children with ASD when compared to controls (Elia et al, 2000; Miano et al, 2007). Parents of children with AUT tend to report elevated rates of sleep problems, but assessment of concurrent sleep behaviors do not consistently complement parental concerns (Goodlin-Jones et al, 2009; Hering, Epstein, Elroy, Iancu, & Zelnik, 1999; Miano et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] PSG and CSHQ Children with regressive ASD ( n = 18) had greater bedtime resistance, sleep-onset latency, and less TST than controls Sivertsen et al [ 31 ] Parent report Prevalence of chronic insomnia was ten times higher in children with ASD symptoms compared to controls Baker et al [ 32 ] Actigraphy and SD Adolescents with ASD were three times more likely to have symptoms of insomnia than their TYP peers Parasomnias Undesirable physical experiences which occur within sleep or during arousal from sleep. Includes nightmares, wake screaming, complex movements, dreams, and automatic nervous system activity Hering et al [ 33 ] Actigraphy and SQ 54% of children with ASD had multiple and early night arousals Doo et al [ 34 ] SQ, CSHQ, and actigraphy All reported evidence of higher rates of parasomnias in children with ASD compared to comparison groups Schreck et al [ 35 ] Liu et al [ 20 ] Goldman et al . [ 36 ] CSHQ Younger children with ASD had more parasomnias than older children Circadian rhythm sleep-wake disorders Alterations of the circadian time-keeping system, its entrainment mechanisms, or misalignment of the endogenous circadian rhythm and the external environment.…”
Section: Reviewmentioning
confidence: 99%